INTERNAL CONTROL SYSTEM IMPLEMENTATION AND EMPLOYEE PERFORMANCE IN THE INDONESIAN BANKING SECTOR - Elkunny Dovir Siratan; Theresia Olivia; Nicky Hermawan; Rini Kus Tresno Ningsih (Journal of Business And Entrepreneurship, 2026)
The goal of this study is to look at how the Internal Control System (ICS) affects employee performance in Indonesian banks. It will focus on the five ICS components that make up the COSO framework. The results show that good ICS implementation has a beneficial effect on staff performance. The five ICS components that particularly govern the environment, risk assessment, control activities, information and communication, and monitoring activities are very important for making the banking sector perform better, increasing efficiency, and reducing mistakes in operations. These results are in line with agency theory, which holds that ICS helps align the interests of management and employees while reducing the risk of moral hazard that could harm performance. Nonetheless, although favorable outcomes were noted, issues related to human factors and adaptation to digital systems indicate that the adoption of ICS in Indonesia’s banking industry warrants additional scrutiny. This study is constrained by its sample, which consists solely of banking personnel in DKI Jakarta, and by its quantitative methodology, which relies on survey data. It is suggested that future studies use a larger sample and a qualitative method and examine the effects of ICS in the context of digital banking, which is becoming increasingly important in today’s tech-savvy world.